Combined lock-in thermography and heat flow measurements for analysing heat dissipation during fatigue crack propagation - J. Baer; A. Vshivkov; O. Plekhov (Fracture and Structural Integrity)
During fatigue crack propagation experiments with constant force as well as constant stress intensity lock in thermography and heat flow measurements with a new developed peltier sensor have been performed. With lock in thermography space resolved measurements are possible and the evaluation allows to distinguish between elastic and dissipated energies. The specimens have to be coated with black paint to enhance the emissivity. The thickness of the coating influences the results and therefore quantitative measurements are problematic. The heat flow measurements are easy to perform and provide quantitative results but only integral in an area given by the used peltier element. To get comparable results the values measured with thermography were summarized in an area equivalent to that of the peltier element. The experiments with constant force show a good agreement between the thermography and the heat flow measurements. In case of the experiments with a constant stress intensity some differences become visible. Whereas the thermography measurements show a linear decrease of the signal with rising crack length, the heat flow measurements show a clearly nonlinear dependency. Obviously the measured energies in thermography and peltier based heat flow measurement are not comparable.